Proximal Adolescent Outcomes of Gang Membership in England and Wales. (March 2014) - Ariza, Juan José Medina; Cebulla, Andreas; Aldridge, Judith; Shute, Jon; Ross, Andy
Objectives: This article aims to apply a "turning points" framework for understanding the developmental impacts of gang membership in a British sample of young people. The study explores the proximal impact of gang membership on offending, victimization, and a number of attitudinal and experiential outcomes that have been theorized to mediate the relationship between gang membership and offending. Method: The authors used data from the Offending Crime and Justice Survey, a rotating panel representative of young people in England and Wales that measured gang membership using the Eurogang definition. The effects of gang membership onset were tested using a propensity score analysis approach. Results: As previously reported with American data, gang onset has an impact on offending, antisocial behavior, drug use, commitment to deviant peers, and neutralization techniques. In addition, gang membership increases the probability of unwanted police contact, even adjusting for offending through a "double robust" procedure. Conclusion: Despite differences in social context, history of gangs and level of violence, we encounter more similarities than differences regarding consequences of gang membership. The impact on unwanted police contact deserves further research and policy attention.